S[k]amtaler : Om etnografisk metode og forskerpositioner - Johansen, Stine Liv; Hansen, Lone Koefoed (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
Researching a phenomenon like the Norwegian TV-series SKAM further complicates the inside-outside notion already debated within ethnographic methods. With SKAM, the reception takes place in a multi-platform and always-on environment: the fan culture(s) happen(s) across several online platforms and the series makes use of a particular understanding of 'liveness' when it updates the story throughout the week, at random times, and on several platforms. This directly influences a researcher's positioning and modes of action. In this paper, we discuss the act of researching SKAM through analysing empirical data from our conversation on Messenger in which we—in the eight months it lasted—acted both as fans or viewers and as researchers aiming to understand SKAM's fandom. In this case of an continuously updating narrative that seems to happen in a parallel universe to our everyday life, what might 'being-there' entail for researchers?, we ask. The methodological perspectives thus discussed here relate to auto-ethnography as well as to media-ethnography, allowing us to discuss how SKAM was a phenomenon that interfered into our professional but definitely also into our private lives.